Ez Top up / Nur Diyana Abd Khalil... [et.al]. - Abd Khalil, Nur Diyana; Mohd Sutrizeno, Nabila Kartini; Hassim, Hanani; Razali, Noor Azimah (2011)
Ez Top up is a prepaid card shop. We are going to setup our business in Ampang Point,Ampang. The location is quite strategic because it is near some housing areas and attracted place. The company is setup based on a partnership agreement between four o f ours partners. The company will be built using the contribution among the partners. Approximately RM 80,000 will be needed to start off our business. From the marketing point o f view, our target market is based on demographic, psychographic and geographic. The age range is between 18% o f the target market from our competitors. We will television and radio. Banners and signboards will help. From the operational point of view, our target market is based on demographic, psychographic and geographic. The age range is between teenagers to adults. we will try to get 18% of the target market from our competitors. we will advertise in newspapers, in a magazine, television and radio. Banners and signboard will help the advertising process to. From the operational point of view, we will have one shift. We will have two workers. The workers have to go through an interview before being selected and will be trained when selected. In this operation process, we will provide the best service possible for the customer. Financially we are looking at the capital being allocated into specific departments. First there is the administration, we have allocated RM 90,065. The fund is being used to buy office equipment and supplies; such as computers, telephones, desks, renovation sand many more. Next in the marketing department, we have allocated RM 3,768. The money allocated is used for promotional purposes. Advertising the store in the newspapers, magazines, signboard, banners, television and radio. Advertising is very important for any company; we must make the people know that we are better than our competitors. Finally, we have allocated RM 28,620 for our operations department. In a nutshell, we are hoping for the best so that the company will grow and maybe opening other outlets around Malaysia. We have really thought this through and we are very confident that our company will succeed. We will try to provide our customers with better services each day. Without our customers, we will be nothing.